2017
DOI: 10.1186/s12870-017-1214-0
|View full text |Cite
|
Sign up to set email alerts
|

Small RNA profiling for identification of miRNAs involved in regulation of saponins biosynthesis in Chlorophytum borivilianum

Abstract: BackgroundMicroRNAs act as molecular regulator of cell signaling, plant growth and development, and regulate various primary and secondary plant metabolic processes. In the present study, deep sequencing of small RNAs was carried out to identify known and novel miRNAs from pharmaceutically important plant, Chlorophytum borivilianum.ResultsTotal 442 known miRNAs and 5 novel miRNAs were identified from young leaf small RNA library. Experimental validation with stem loop RT-PCR confirmed the in silico identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 54 publications
0
9
0
1
Order By: Relevance
“…Polyploid plants can change gene expression and alter phenotype, thereby favoring themselves for developing phenotypic innovation [18]. In addition, some miRNAs are major biological factors regulating metabolite synthesis in plants [19]. Therefore, to gain a more complete picture, the metabolome and transcriptome data of two cytotypes of S. canadensis roots provide insight into the regulation of gene expression with metabolic networks.…”
Section: Introductionmentioning
confidence: 99%
“…Polyploid plants can change gene expression and alter phenotype, thereby favoring themselves for developing phenotypic innovation [18]. In addition, some miRNAs are major biological factors regulating metabolite synthesis in plants [19]. Therefore, to gain a more complete picture, the metabolome and transcriptome data of two cytotypes of S. canadensis roots provide insight into the regulation of gene expression with metabolic networks.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the conserved M. koenigii miRNAs were distributed in 34 families, with miR166 as the family with the highest number of members (16) and the highest number of total reads (2795) compared to other families. Kajal and Singh [ 43 ] reported that miR166i-3p was involved in regulating sesquiterpenes and triterpenoids targeting the squalene synthase in Chlorophytum borivilianum , which produces a type of saponins known as borivilianosides, with several pharmacological activities such as immunomodulatory, antidiabetic, and androgenic. However, in contrast, it has been reported that the miR166 family from blueberry ( Vaccinium ashei ) can target the transcription factor squamosa promoter binding protein-like (SPL), which prevents the expression of the biosynthetic genes of anthocyanins flavonoid [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, miR159, miR172 from roots, and miR530 from leaves were involved in the regulation of secondary metabolite associated with mRNAs [54]. Chlorophytum borivilianum, Oryza sativa, and Arabidopsis thaliana target gene prediction indicate that miR9662, miR894, miR172, and miR166 might be involved in regulating saponin biosynthetic pathway [55]. miR8154 and miR5298b increase taxol, phenylpropanoid, and flavonoid biosynthesis in subcultured Taxus cells [56].…”
Section: Other Secondary Metabolitesmentioning
confidence: 96%